2022
DOI: 10.1108/ijmpb-12-2021-0329
|View full text |Cite
|
Sign up to set email alerts
|

The impact of authentic leadership on project success: the mediating effect of organizational learning and innovation

Abstract: PurposeThe study exemplifies authentic leadership (AL) and relates it to project success (PS) with the mediating variables of organizational learning (OL) and organizational innovation (OL). None of the existing studies on AL and PS have worked on the mediation of OL and OI on these factors. So far, this paper tries to fill gap between these factors.Design/methodology/approachThe study is done by testing the hypothesis by utilizing the approach of deduction. The tool of data collection utilized is a survey. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This hypothesis focus on studying the effect of authentic leadership using its dimensions (self-awareness, relational transparency, balanced processing, and internalized moral perspective) as an independent variable on academic staff performance. Such as (Kurian & Nafukho, 2022;Arokiasamy et al, 2022 ;Nawaz & Tian, 2022;Duarte et al, 2021;Llorens et al, 2021;Astuti et al, 2020;Soares & Lopes, 2020 ;Supriyadi et al, 2020;Aropah & Sumertajaya, 2020;Asbari et al, 2019;Alzghoul et al, 2018;Ahmad et al, 2015) previous studies indicated that authentic leadership affect on academic staff performance. Accordingly, the first main hypothesis states: H1: "There is a statistically significant effect of authentic leadership on academic staff's performance in Upper Egypt Universities " This hypothesis has four relevant sub-hypotheses:…”
Section: Hypothesis Onementioning
confidence: 99%
“…This hypothesis focus on studying the effect of authentic leadership using its dimensions (self-awareness, relational transparency, balanced processing, and internalized moral perspective) as an independent variable on academic staff performance. Such as (Kurian & Nafukho, 2022;Arokiasamy et al, 2022 ;Nawaz & Tian, 2022;Duarte et al, 2021;Llorens et al, 2021;Astuti et al, 2020;Soares & Lopes, 2020 ;Supriyadi et al, 2020;Aropah & Sumertajaya, 2020;Asbari et al, 2019;Alzghoul et al, 2018;Ahmad et al, 2015) previous studies indicated that authentic leadership affect on academic staff performance. Accordingly, the first main hypothesis states: H1: "There is a statistically significant effect of authentic leadership on academic staff's performance in Upper Egypt Universities " This hypothesis has four relevant sub-hypotheses:…”
Section: Hypothesis Onementioning
confidence: 99%
“…PBOs in the construction industry are usually operated within an established network structure and communication channels and facilitate the innovation process through knowledge sharing. On the one hand, organization innovation will improve task performance as well as project success [70]; on the other hand, the innovation process will take time, which is in contradiction with the time limitations for task completion of a construction project [71]. Could bootleg innovation be a strategy to resolve this paradox?…”
Section: The Mediator Of Bootleg Innovation Behaviormentioning
confidence: 99%
“…Employees engage in organizational activity and involvement in decision-making that makes an employee feel a sense of belonging and try their best to achieve the organizational objective (Sane ́ et al, 2021). Manager with the democratic leadership style establishes a better relationship with the staff by giving freedom and reducing the work tension which leads to directing their subordinates toward their thoughts and ideas regarding establishing ability to achieve the objective (Kabore et al, 2021;Nawaz & Tian, 2022).…”
Section: Democratic Leadership Stylementioning
confidence: 99%